A systematic review of multi-level intervention to enhance the quality of life patient with human immunodeficiency virus - Yuntari, Gusti Ayu Krisma; Ady Wirawan, I Made; Sri Budayanti, Ni Nyoman; Arimbawa, Putu Eka (Intelektual Pustaka Media Utama, 2024)
Human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) are still challenges worldwide. Improvement in quality of life (QoL) is crucial for HIV-infected people. The QoL of HIV-infected patients has been improved by the use of multilevel interventions in various circumstances. This study evaluates the evidence for interventions that target the quality of life of persons with HIV. A systematic review was performed according to the PRISMA guidelines. Science Direct, the Cochrane Library database, and Pubmed were also searched. Three independent reviewers extracted the data. Searches were conducted for articles published from 2013 to 2023. Searching procedures and data abstraction techniques were standardized. The 27 research examined the effects of interventions on HIVinfected people's quality of life. China is the most frequently mentioned country in the 27 studies, appearing as the setting in 8 (29.6%). Following South Africa (14.8%), New York (11.11%) and Kenya (7.4%) were the next most often mentioned countries. For analysis purposes, the interventions used in the 27 reviewed studies were classified into three main categories: individual intervention, family-community intervention, and health service intervention. Significant intervention innovations in quality-of-life research combining several interventions, including individual, family, community, and health system intervention, show the most promising results